مصارف الزكاة في بيت المال بترنجانو : دراسة تطبيقية تحليلية - Ummi Fairuz Razak (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research aims to analyze the understanding of the eight recipients of zakah and Islamic law (ahkam syariʻyyah) related to collecting and distributing zakah according to Islamic scholars and what is applied in Baitul Mal Terengganu. It also includes a discussion on the three recipients of zakah on which an on-going debate continues; those who embrace Islam, slaves and those fighting in the path of Allah. Moreover, this research studies the history and administration of Baitul Mal Terengganu. The research methods were based on inductive and analytical approaches. The inductive analytical methods were done through the study of the eight recipients of zakah from different types of scholarly books, and issues related to this topic which were based on current and classical references. Besides that, the researcher gathered information from Baitul Mal Terengganu. The data consisted of data on the collection and distribution of zakah and types of zakah assistance to the eight recipients. The data and information were discussed and analyzed according to Islamic Jurisprudence. Data and information on collection of zakah and its distribution were discussed and analyzed during a six-year period was taken from 2008-2013. Thus, it was found that this institution played its role as the guardian of zakah properties according to Islamic Jurisprudence, the eight recipients of zakah as well as the way they collected and distributed zakah. However, it also found that there were several problems in managing and controlling types of zakah assistance. Besides that, there were limited workers as well as lack of professionalism and knowledge among officers in management, especially in Islamic Jurisprudence knowledge. Based on this, the researcher highlights the importance of creating a Syariah Committee in Baitul Mal in order to ensure that Islamic law (ahkam syariʻyyah) is applied in Baitul Mal, conforming to Islamic legitimacy. Besides that, to overcome the problem of worker shortage, Baitul Mal could cooperate with other bodies or individuals like non-governmental organizations and head-villagers or imam of mosque in order to identify and get information on zakah recipients.